Ambiguous effects of anti-VEGF monoclonal antibody (bevacizumab) for POEMS syndrome. Issue 12 (5th March 2013) - Sekiguchi, Yukari; Misawa, Sonoko; Shibuya, Kazumoto; Nasu, Saiko; Mitsuma, Satsuki; Iwai, Yuta; Beppu, Minako; Sawai, Setsu; Ito, Shoichi; Hirano, Shigeki; Nakaseko, Chiaki; Kuwabara, Satoshi
Abstract : Objective: Vascular endothelial growth factor (VEGF) plays an essential role in the pathophysiology of polyneuropathy, organomegaly, endocrinopathy, M-protein and skin changes (POEMS) syndrome. Anti-VEGF antibody (bevacizumab) appears to be an attractive therapeutic option. The aim of this study is to investigate the effects of bevacizumab for patients with POEMS syndrome. Methods: We reported six POEMS patients treated with bevacizumab and reviewed the literature. Results: The serum VEGF levels decreased immediately after bevacizumab administration in all six patients. However, four patients had entirely no clinical response, and two of them died. The remaining two showed improvement that could be explained by combined treatments. We also reviewed the literature and found 11 patients treated with bevacizumab; of these, only one was treated with bevacizumab alone. 10 had combined treatments, and four died without any response. Conclusions: Both our experience and the literature suggest ambiguous effects of bevacizumab; inhibition of VEGF alone may be insufficient because multiple cytokines are upregulated, or aberrant neo-vascularization may have already fully developed in the advanced stage of POEMS syndrome.